PENGARUH BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP DISIPLIN KERJA PEGAWAI DI RSAU DR. ESNAWAN ANTARIKSA JAKARTA - Dewijanty Maya Kartika,; Wahyudi Bayu,; Veranita Mira, (Journal of Innovation Research and Knowledge, 2025)
This study aims to determine the influence of organizational culture and work motivation on employee work discipline at RSAU dr. Esnawan Antariksa Jakarta. This study uses a quantitative method. The sample in this study was taken as many as 230 people. The sampling technique in this study used accidental sampling, namely taking samples that happened to be there and available when the study was conducted. In testing the hypothesis in this study using multiple linear regression tests. The results of the study showed that there was a positive and significant influence between organizational culture on employee work discipline, and there was a positive and significant influence between work motivation on employee work discipline and there was a positive and significant influence between organizational culture and work motivation on employee work discipline at RSAU dr. Esnawan Antariksa